(untitled) (Research, Society and Development, 2020)
The objective of this work was to evaluate the influence of different proportions of jambolan pulp, sugar and water on the physical and chemical characteristics to obtain information that allows the use of jambolan and, consequently, the evaluation of these fruits. Six jambolan nectar formulations were established through Simplex design. Ingredients significantly affected luminosity (32,14-34,24), apparent viscosity (7.8-73.8 cP), total soluble solids (8.87-26.43 °Brix), titratable acidity (0.55 -0.83g citric acid 100g-1) and the TSS / TA ratio (16.05-34.96) in jambolan nectars. Jambolan nectar with 55g 100g-1 of jambolan pulp, 15g 100g-1 of sugar and 30g 100g-1 of water has the highest desirability in relation to physical and physicochemical properties, 85.1% DPPH inhibition, 10526.12 μg TE mL-1 and 27014.25 μmol TE mL-1 by ABTS and ORAC method, respectively. It could be concluded that it is possible to produce jambolan nectar which can increase the possibilities of applying fruit as an ingredient in the food industry.